1995
DOI: 10.1021/bi00013a007
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and Circular Dichroism Analysis of the C-Terminal Signal Peptides of HlyA and LktA

Abstract: The secretion of the 107 kDa hemolysin A (HlyA) from Escherichia coli is mediated by membrane proteins hemolysin B (HlyB) and hemolysin D (HlyD). The signal for transport has been mapped to the C-terminal 60 amino acids of the HylA molecule. We have shown previously that the C-terminal 70 amino acids of leukotoxin (LktA) from Pasteurella hemolytica can substitute functionally for the HlyA signal sequence. This 70 amino acid peptide contains little primary sequence similarity to the HlyA signal sequence, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…Moreover, these data suggest, as we previously proposed, that the functional secretion signal could be unfolded when it is presented to the translocation apparatus. The unfolded nature of the signal region in vivo indicated by genetic studies is supported by a recent circular dichroism analysis of the C-terminal, 60-residue peptide of HlyA, which indicates that the peptide adopts a predominantly random conformation in aqueous solution (27). The same study indicated that this peptide adopts a helical secondary structure in the presence of sodium dodecyl sulfate or anionic phospholipids, and a more recent nuclear magnetic resonance analysis (25) detected ␣-helical structures close to the position of the predicted ␣-helices I and II.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, these data suggest, as we previously proposed, that the functional secretion signal could be unfolded when it is presented to the translocation apparatus. The unfolded nature of the signal region in vivo indicated by genetic studies is supported by a recent circular dichroism analysis of the C-terminal, 60-residue peptide of HlyA, which indicates that the peptide adopts a predominantly random conformation in aqueous solution (27). The same study indicated that this peptide adopts a helical secondary structure in the presence of sodium dodecyl sulfate or anionic phospholipids, and a more recent nuclear magnetic resonance analysis (25) detected ␣-helical structures close to the position of the predicted ␣-helices I and II.…”
mentioning
confidence: 86%
“…Such blocks of repeats, which define the so-called RTX toxins (24), can occur variously from 70 to 150 residues from the C terminus, and the number of RTX repeats can also vary from 5 to 7 to up to at least 33. In several cases, in addition to HlyA, direct evidence for the presence of a C-terminal secretion signal has been obtained (3,8,17,21,26,27). Moreover, albeit with various degrees of efficiency, translocators can be exchanged and secretion of heterologous toxins or proteases can be demonstrated, with the E. coli HlyBD translocator being particularly promiscuous in this respect (see, for example, references 3, 4, 11, 20, and 26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical experiments showed that the signal sequences, known to interact with the transporter [60], formed amphiphilic helices only in the presence of lipids. This suggested that HlyB might recognise its substrate within the inner leaflet of the membrane [76]. We were eventually able to replace the HlyA signal entirely with random synthetic sequences and showed that only a resemblance to the native signal in charge and amphiphilicity, not in primary sequence, was required [24].…”
Section: P-glycoprotein and The Search For A Central Dogma Of Mdrmentioning
confidence: 97%
“…An obvious signal for targeting was also believed to exist in the T1SS, whose substrates carry a noncleavable C-terminal signal able to bind the ABC component of the T1SS. This signal does not have a conserved amino acid sequence but has a helical secondary structure spanning about 30 to 60 residues that, in principle, cannot be removed without loss of targeting/secretion (27). However, studies in the laboratory of Cécile Wandersman have previously shown that the T1SS-dependent HasA substrate from Serratia marcescens can be efficiently targeted to the secretion machinery despite lacking 14 C-terminal amino acids (6).…”
mentioning
confidence: 99%